3

I'm entirely unfamiliar with the syntax and corresponding semantics Davidson uses for the four equations at the beginning of Truth and Meaning. He states that the following sentences are supposed to be equivalent in some invalid theory, but I'm not sure what two of them are even supposed to mean in the naive theory. The four sentences are:

(1) R
(2) x̂(x=x.R)=x̂(x=x)
(3) x̂(x=x.S)=x̂(x=x)
(4) S

His conclusion is that the naive (possibly Fregian?) theory doesn't work because it says that all sentences with the same truth value must me synonymous. I get that that is an odd result, but I don't understand what these four equations are communicating to get that result. Thanks for the help!

2

The phrase x̂(x=x) means 'the x such that x=x'. This is just a way of forming a singular term that refers to something. The . is conjunction ('and').

So x̂(x=x.R)=x̂(x=x) is logically equivalent to R. And, since R is logically equivalent to S (by assumption), both x̂(x=x.R) and x̂(x=x.S) refer to the same thing. And then x̂(x=x.R)=x̂(x=x) and x̂(x=x.S)=x̂(x=x) refer to the same thing. This is how Davidson gets to the conclusion that any two sentences have the same reference if they are logically equivalent.

Your Answer

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.